Analisis Pengaruh Sosial CRM Terhadap Loyalitas Customer Pada Layanan Pengguna Aplikasi DANA - Ali Ibrahim; Oktrioka Gisbu; Erinne Rizky Salsadila; Rahmat Fitra Arkamil; M Aditya Wijaya; M Hafadz Raihan (STMIK Budi Darma, 2022)
DANA application is one of the digital wallet applications which of course has a function as a tool for making payments. Funds can be used by all ages, besides that, funds are also very much needed today as a digital wallet. Transactions using Dana can be done anywhere, such as shops, restaurants, or online shopping payments. With the development of information technology, Dana is required to always provide services that can complete online transactions. Digital or online transactions have become a part of modern society's life. A good application is an application that can make users satisfied with the services provided because that is the purpose of the Fund Application. The research methodology used is a quantitative survey research method that describes the causal relationship and the effect that occurs between the existing variables using hypothesis testing. Customer Relationship Management (CRM) is a strategy used to analyze data, consolidate, and also obtain data which is then used to interact with customers (Dana application users), with this it will produce a comprehensive view of customers and customer satisfaction on Application services. Fund.